Trisomy chromosome 5 is a recurrent cytogenetic lesion in mammary tumors from parous MMTV-erbB-2 transgenic mice - KIM, YOUNG MI (D.A. Spandidos, 2011)
erbB-2 is amplified or overexpressed in approximately 30% of human breast cancers, and has been associated with poor prognosis and therapeutic resistance. Previous studies have suggested that erbB-2 overexpression in transgenic mice induces genomic instability; however, the patterns of genetic lesions vary with individual model systems. The development of mammary tumors in multiparous murine mammary tumor virus (MMTV)-erbB-2 transgenic mice is accelerated due to hormonal interactions which induce the overexpression of MMTV-mediated erbB-2. However, whether or not accelerated tumor development is associated with modified cytogenetic patterns remains to be determined. In this study, chromosomal changes were characterized in mammary tumor cells derived from multiparous MMTV-erbB-2 transgenic mice, and compared with tumor cells derived from control virgin mice. Immunohistochemistry and Western blotting were used to detect erbB-2 overexpression in mammary tissues. Each of the five tumors from the multiparous MMTV-erbB-2 transgenic mice was found to exhibit a marked chromosomal imbalance, compared with only one tumor with aberrant chromosomes among the five tumors from the control virgin mice. In particular, trisomy 5 and loss of the X chromosome were recurrent cytogenetic lesions in tumors from the parous mice, which is a novel pattern compared with previous studies. The elevated number of genetic lesions in tumors from parous mice, which were characterized by enhanced erbB-2 overexpression and increased receptor tyrosine kinase activation in the mammary glands, suggest a causal role for erbB-2 in the genomic instability present in these tumors. These data advance our understanding of erbB-2-mediated pathogenesis and underscore the role of cytogenetic alteration in this process.